Utilizing Coal Ash and Humic Substances as Soil Ameliorant on Reclaimed Post-Mining Land - Ade Mariyam Oklima; . Sudarsono; . Iskandar; Dyah Tjahyandari Suryaningtyas (JOURNAL OF TROPICAL SOILS, 2014)
Coal ash and humic substances can be used as soil ameliorant in the reclamation of formerly mined land. Due to its high pH and nutrients content, coal ash can be used to improve the chemical properties of the soil, such as increasing of pH, and increasing the levels of nutrients availability in the soil. Humic substances may also be used to complement, as they can increase the release of nutrients from the coal ash. Thus, the objective of this study was to assess the influence of coal ash and humic substances on soil chemical characteristics, nutrient absorption, and plant growth. This study was conducted in two locations - in a nursery area, involving two treatment factors: coal ash at different dosages (0, 200, and 400 g polybag-1), and humic material also at varying dosages (0, 0.04, and 0.08 g C polybag-1); and in a post-mining field using similar treatments: coal ash dosage (0, 2.5, and 5.0 kg planting-1 hole) and humic material dosage (0, 0.56, and 1.12 g C planting hole-1). The results showed that coal ash and humic materials significantly increased the soil pH, available P, and exchangeable K, Ca and Mg. Coal ash also contained a number of heavy metals but in quantities that are far below the limits set by both Indonesian Government Regulation and the US Environmental Protection Agency (USEPA). The above soil amelioration effects mean that. applicaton of coal ash and humic substances can significantly increase the growth of Jabon trees in the reclaimed post-mining land.[How to Cite: Ade MO, Sudarsono, Iskandar and DT Suryaningtyas. 2014. Utilizing Coal Ash and Humic Substances as Soil Ameliorant on Reclaimed Post-Mining Land. J Trop Soils 19: 161-169. Doi: 10.5400/jts.2014.19.3.161] [Permalink/DOI: www.dx.doi.org/10.5400/jts.2014.19.3.161]